2020
DOI: 10.1523/jneurosci.2902-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Desire or Dread from Nucleus Accumbens Inhibitions: Reversed by Same-Site Optogenetic Excitations

Abstract: Microinjections of a glutamate AMPA antagonist (DNQX) in medial shell of nucleus accumbens (NAc) can cause either intense appetitive motivation (i.e., 'desire') or intense defensive motivation (i.e., 'dread'), depending on site along a flexible rostrocaudal gradient and on environmental ambience. DNQX, by blocking excitatory AMPA glutamate inputs, is hypothesized to produce relative inhibitions of NAc neurons. However, given potential alternative explanations, it is not known whether neuronal inhibition is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
0
6
0
3
Order By: Relevance
“…As part of the mesolimbic reward pathway between the prefrontal cortex and the emotional limbic system, the NAcc facilitates subjective experiences of pleasure when introduced to favorable stimuli. Studies have shown that stimulation of the NAcc can effectively increase feeding behavior of rats (Baumgartner et al, 2020). Additionally, deep brain stimulation technologies that increase neural firing in the NAcc are approved for the treatment of depression in humans by relieving symptoms of anhedonia (lack of pleasure) (Delaloye & Holtzheimer, 2014).…”
Section: History Of Mind Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of the mesolimbic reward pathway between the prefrontal cortex and the emotional limbic system, the NAcc facilitates subjective experiences of pleasure when introduced to favorable stimuli. Studies have shown that stimulation of the NAcc can effectively increase feeding behavior of rats (Baumgartner et al, 2020). Additionally, deep brain stimulation technologies that increase neural firing in the NAcc are approved for the treatment of depression in humans by relieving symptoms of anhedonia (lack of pleasure) (Delaloye & Holtzheimer, 2014).…”
Section: History Of Mind Controlmentioning
confidence: 99%
“…Because optogenetics allows instant and selective stimulation of any brain area, optogenetic neurons in the NTS and NAcc could be stimulated to decrease or increase desired behaviors. A study by Baumgartner et al (2020) tested optogenetic stimulation in mice. The study used CRISPR to implant opsins in different areas of the NAcc and found that, depending on the location of stimulation, both desire and dread could be reliably induced by optogenetic stimulation (Baumgartner et al, 2020).…”
Section: Optogenetics and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAc is a critical hub involved in motivation for various rewards, such as food and drugs of abuse, as well as fear and aversion [ 4 , 5 ]. The NAc is primarily comprised of medium spiny neurons (MSNs) of two distinct subpopulations: D1-MSNs and D2-MSNs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus accumbens (NAc) mitochondrial fission or molecules related to mitochondrial dynamics and function are altered by cocaine 1,2 . The NAc is a critical hub involved in motivation for various rewards, such as food, sex, and drugs of abuse, as well as fear and aversion 4,5 .…”
Section: Introductionmentioning
confidence: 99%